The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.seta.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Specification of energy assessment methodologies to satisfy ISO 50001 energy management standard

Abstract: Specification of Energy Assessment Methodologies to Satisfy Energy Management Standard Harish KannegantiEnergy management has become more crucial for industrial sector as a way to lower their cost of production and in reducing their carbon footprint. Environmental regulations also force the industrial sector to increase the efficiency of their energy usage. Hence industrial sector started relying on energy management consultancies for improvements in energy efficiency. With the development of ISO 50001 standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 10 publications
0
32
0
4
Order By: Relevance
“…Since the first industrial revolution, the use of energy has grown significantly. The replacement of handwork by machines has enabled the manufacturing sector to dictate the pace of economic growth, and the use of energy played an essential role in this [22]. Currently, considering only the industrial and commercial sectors, energy use is responsible for almost 40% of greenhouse gas emissions [23].…”
Section: Targets Of the Seventh Goalmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first industrial revolution, the use of energy has grown significantly. The replacement of handwork by machines has enabled the manufacturing sector to dictate the pace of economic growth, and the use of energy played an essential role in this [22]. Currently, considering only the industrial and commercial sectors, energy use is responsible for almost 40% of greenhouse gas emissions [23].…”
Section: Targets Of the Seventh Goalmentioning
confidence: 99%
“…In this sense, energy management systems are important in their ability to support organizations seeking to increase energy efficiency and minimize their negative environmental impact [17,31,32]. In this context, the standard ISO 50001 performs an important role in guiding organizations to implement an energy management system [15,22]. Presenting a structure increasingly similar to the others ISO (International Organization for Standardization) standards, the integration of ISO 50001 with them is facilitated [33].…”
Section: Targets Of the Seventh Goalmentioning
confidence: 99%
See 1 more Smart Citation
“…Gopalakrishnan [35] developed an energy analyzer software to facilitate the application and the certification of ISO 50001 in industrial facilities. Other such examples of implementing industrial energy management and standards can readily be found in literature [36][37][38]. May et al [28] reviewed literature from 1995 to 2015, and identified four key aspects of energy management for manufacturing, one of which are the tools and methods that support energy management, see Figure 1.…”
Section: Energy Management Standardsmentioning
confidence: 99%
“…The current research guidelines focus on studies related to energy management performance, based on the ISO Standard 50001. The development of the ISO Standard 50001 and energy management have attracted the attention of senior management of industry towards implementing continuous improvement processes, as stated by Kanneganti et al [22]. Regarding the implementation of the standard's guidelines, Pelser et al [23] developed and implemented an energy performance report covering the verification of ISO Standard 50001, in a South African cement plant where the cost of electricity was reduced by 25%.…”
Section: Introductionmentioning
confidence: 99%